Political assassins, terrorists and related conspiracies in American history - Johnson, Scott Patrick (McFarland & Company, Inc., Publishers, 2021)
""Political assassinations and terrorism have both outraged and fascinated the public throughout American history, particularly in the modern era. Providing biographical summaries of more than 100 assassins and terrorists, this book aims at a more complete understanding of the motivations behind violent extremism. The lives of the subjects are analyzed with a focus on psychological and ideological factors, along with details of investigations and criminal trials. Conspiracy theories are evaluated for credibility. Social media features prominently in explaining political violence by members of extremist groups in the 21st century, including radical Islamic terrorists, anti-abortion activists and white supremacists."-Provided by publisher"--